The cuprizone-induced changes in 1H-MRS metabolites and oxidative parameters in C57BL/6 mouse brain: Effects of quetiapine. (November 2015) - Xuan, Yinghua; Yan, Gen; Wu, Renhua; Huang, Qingjun; Li, Xinmin; Xu, Haiyun
Abstract: Cuprizone is a copper-chelating agent and able to induce oligodendrocyte loss and demyelination in C57BL/6 mouse brain. Recent studies have used the cuprizone-fed mouse as an animal model of schizophrenia to examine putative roles of altered oligodendrocytes in this mental disorder. The present study reported the effects of cuprizone on the brain metabolites and oxidative parameters with the aim of providing neurochemical evidence for the application of the cuprizone mouse as an animal model of schizophrenia. In addition, we examined effects of quetiapine on the cuprizone-induced changes in brain metabolites and oxidative parameters; this atypical antipsychotic was shown to ameliorate the cuprizone-induced demyelination and behavioral changes in previous studies. C57BL/6 mice were fed a standard rodent chow without or with cuprizone (0.2% w/w) for four weeks during which period they were given sterilized saline or quetiapine in saline. The results of the proton magnetic resonance spectroscopy (1H-MRS) showed that cuprizone-feeding decreased 1 H-MRS signals of N-acetyl-l -aspartate (NAA), total NAA (NAA + NAAG), and choline-containing compounds (phosphorylcholine and glycerophosphorylcholine), suggestive of mitochondrial dysfunction in brain neurons. Biochemical analyses showed lower activities of catalase and glutathione peroxidase, but higher levels of malondialdehyde and H2 O2 in the brain tissue of cuprizone-fed mice, indicative of an oxidative stress. These cuprizone-induced changes were effectively relieved in the mice co-administered with cuprizone and quetiapine, although the antipsychotic alone showed no effect. These findings suggest the toxic effects of cuprizone on mitochondria and an antioxidant capacity of quetiapine, by which this antipsychotic relieves the cuprizone-induced mitochondrial dysfunction in brain cells. Highlights: Cuprizone-feeding increased levels of MDA and H2 O2 . Cuprizone-feeding decreased activities of catalase and GPx. Cuprizone-feeding decreased 1 H-MRS signal of NAA, tNAA, and tCho in the brain. Quetiapine ameliorated the cuprizone-induced MRS signal change and oxidative stress.